Equilibrium liquidity premia of private equity funds. Issue 1 (18th January 2016) - Buchner, Axel
Abstract : Purpose: – The purpose of this paper is to propose a novel theory of the equilibrium liquidity premia of private equity funds and explore its asset-pricing implications. Design/methodology/approach: – The theory assumes that investors are exposed to the risk of facing surprise liquidity shocks, which upon arrival force them to liquidate their positions on the secondary private equity markets at some stochastic discount to the fund's current net asset value. Assuming a competitive market where fund managers capture all rents from managing the funds and investors just break even on their positions, liquidity premia are defined as the risk-adjusted excess returns that fund managers must generate to compensate investors for the costs of illiquidity. The model is calibrated to data of buyout funds and is illustrated by using numerical simulations. Findings: – The model analysis generates a rich set of novel implications. These concern how fund characteristics affect liquidity premia, the role of the investors' propensities of liquidity shocks in determining liquidity premia and the impact of market conditions and cycles on liquidity premia. Originality/value: – This is the first paper that derives liquidity premia of private equity funds in an equilibrium setting in which investors are exposed to the risk of facing surprise liquidity shocks.